Interactive Digital Learning Content of Healthy Food for Children - Mohamed, Hasiah; Hidayah Fatihah Rohan, Nur; Nur Balqis Lokman, Siti; Syuhada Hasan, Nur; Adilin Mohd Abd Majid, Hayati; Aziz, Nurulnadwan (International Journal of Engineering and Technology, 2018)
Since past, parents facing difficulties in introducing the healthy food for their children. Usually, the children setting their mind that healthy food contain a bad taste. The similar situation also faces by teachers in kindergarten or child-care institution, in educating and encouraging the children to eat healthy food. Naturally, most of the children were more attracted to unhealthy food particularly junk food which contains high calories and sugar. Due to that, eating healthy food has to be taught to children since they are in young age particularly in kindergarten to ensure they are keep healthy. Thus, to overcome the problem this study proposes an interactive digital content of healthy food for children namely Saya Sihat. The design science research methodology which consists of five (5) phases: (i) problem identification, (ii) content analysis, (iii) design and development, (iv) evaluation, and (v) documentation have been adopted. Meanwhile, user-centered design approach has been utilized throughout the development of the proposed application since it is important for this study to obtain the optimum input from parents and teachers as well as children as the main target users. Testing has been conducted to 30 respondents in terms of the usefulness of multimedia elements integrated in the proposed interactive digital content. It was found that all the integrated elements meet the user needs and the proposed interactive digital content able to evoke the positive mindset of healthy food to children.Â Â Â Â